Effect of Perceptual Load on Semantic Access by Speech in Children. - Jerger, Susan; Damian, Markus F.; Mills, Candice; Bartlett, James; Tye-Murray, Nancy; Abdi, Hervé; Bacon, Sid; Goldinger, Steve (Journal of Speech, Language & Hearing Research, 2013)
Purpose: To examine whether semantic access by speech requires attention in children. Method: Children (N = 200) named pictures and ignored distractors on a cross-modal (distractors: auditory-no face) or multimodal (distractors: auditory-static face and audiovisual- dynamic face) picture word task. The cross-modal task had a low load, and the multimodal task had a high load (i.e., respectively naming pictures displayed on a blank screen vs. below the talker's face on his T-shirt). Semantic content of distractors was manipulated to be related vs. unrelated to the picture (e.g., picture "dog" with distractors "bear" vs. "cheese"). If irrelevant semantic content manipulation influences naming times on both tasks despite variations in loads, Lavie's (2005) perceptual load model proposes that semantic access is independent of capacity-limited attentional resources; if, however, irrelevant content influences naming only on the cross-modal task (low load), the perceptual load model proposes that semantic access is dependent on attentional resources exhausted by the higher load task. Results: Irrelevant semantic content affected performance for both tasks in 6- to 9-year-olds but only on the cross-modal task in 4- to 5-year-olds. The addition of visual speech did not influence results on the multimodal task. Conclusion: Younger and older children differ in dependence on attentional resources for semantic access by speech.